Absence of Stress Hyperglycemia Indicates the Most Severe Form of Blunt Liver Trauma - Janett Kreutziger; Margot Fodor; Dagmar Morell-Hofert; Florian Primavesi; Stefan Stättner; Eva-Maria Gassner; Stefan Schmid; Christopher Rugg (Diagnostics, 2021)
Background: Stress hyperglycemia is common in trauma patients. Increasing injury severity and hemorrhage trigger hepatic gluconeogenesis, glycogenolysis, peripheral and hepatic insulin resistance. Consequently, we expect glucose levels to rise with injury severity in liver, kidney and spleen injuries. In contrast, we hypothesized that in the most severe form of blunt liver injury, stress hyperglycemia may be absent despite critical injury and hemorrhage. Methods: All patients with documented liver, kidney or spleen injuries, treated at a university hospital between 2000 and 2020 were charted. Demographic, laboratory, radiological, surgical and other data were analyzed. Results: A total of 772 patients were included. In liver (n = 456), spleen (n = 375) and kidney (n = 152) trauma, an increase in injury severity past moderate to severe (according to the American Association for the Surgery of Trauma, AAST III-IV) was associated with a concomitant rise in blood glucose levels independent of the affected organ. While stress-induced hyperglycemia was even more pronounced in the most severe forms (AAST V) of spleen (median 10.7 mmol/L, p < 0.0001) and kidney injuries (median 10.6 mmol/L, p = 0.004), it was absent in AAST V liver injuries, where median blood glucose level even fell (5.6 mmol/L, p < 0.0001). Conclusions: Absence of stress hyperglycemia on hospital admission could be a sign of most severe liver injury (AAST V). Blood glucose should be considered an additional diagnostic criterion for grading liver injury.